Transactions on computational collective intelligence IX - Nguyen, Ngoc Thanh (Lecture notes in computer science, 2013)
These transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the semantic Web, social networks and multiagent systems. TCCI strives to cover new methodological, theoretical, and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This ninth issue contains ten carefully selected and thorougly revised contributions.